White matter alterations in the corpus callosum of adolescents with first-admission schizophrenia - Henze, Romy; Brunner, Romuald; Thiemann, Ulf; Parzer, Peter; Resch, Franz (Neuroscience letters, 2012)
Several diffusion tensor imaging (DTI) studies involving adults and adolescents with schizophrenia have examined fractional anisotropy (FA) in the corpus callosum (CC) with conflicting findings. This may be due to confounding factors such as the chronicity of the disorder, long-term medication with psychotropics or methodological differences. To provide a clearer picture of early alterations, we examined 13 adolescents with first-admission schizophrenia and 13 healthy controls using a region-of-interest approach based on probabilistic voxel classification. We quantified FA in four subdivisions of the CC and hypothesized that adolescents with schizophrenia display a reduced FA in the genu associated with ‘hypofrontality’ and a reduced FA in the body of the CC linked to the heteromodal association cortex. Fiber integrity measurements revealed significant FA decreases in the genu and body of the CC in adolescents with schizophrenia compared to healthy controls. These findings emphasize the central role of the CC in even the early stages of schizophrenia and lend weight to hypotheses about frontal alterations and the central role of the heteromodal association cortex in the aetiopathogenesis of the disorder.